Implementasi Pompa Air Dengan Tenaga Surya Untuk Kebutuhan Air Di Pemakaman Karang Bendo Bantul - Trisuryani, Slamet Hani; Santoso, Gatot; Kristiyana, Samuel; Agus Pratama, Wahyu Maulidi (LPPM IST AKPRIND Yogyakarta, 2023)
Every life is never separated from the need for water because water is a basic need, especially for humans, both for drinking, bathing, and at the time of pilgrimages to tombstones they the visit. Meanwhile, to get the water, the community lifts it from the nearest water source, namely a healthy water source, which is done manually by drawing water and putting it into a water reservoir. Suppose done enough draining continuously. In addition, to get a power source at the burial site, the community takes electricity from the nearest power source or residents' homes. However, this can be overcome by using an alternative solar power generation system as a driving force for a water pump to lift DC water designed portable to meet water needs. By doing a design using two solar panels of 100watt peak, a solar charge controller with a capacity of 20 amperes and a battery unit with a total of 20Ah able to lift water from the well to a water reservoir 89.034 liters in 8 minutes. The electrical energy required for single use of the water pump is 23.4 Wh, so it is expected to increase the use of time, energy, and the volume of clean water to be more efficient.